Sex‐biased gene expression in dioecious garden asparagus (Asparagus officinalis). Issue 3 (27th March 2015) - Harkess, Alex; Mercati, Francesco; Shan, Hong‐Yan; Sunseri, Francesco; Falavigna, Agostino; Leebens‐Mack, Jim
Summary: Sex chromosomes have evolved independently in phylogenetically diverse flowering plant lineages. The genes governing sex determination in dioecious species remain unknown, but theory predicts that the linkage of genes influencing male and female function will spur the origin and early evolution of sex chromosomes. For example, in an XY system, the origin of an active Y may be spurred by the linkage of female suppressing and male promoting genes. Garden asparagus ( Asparagus officinalis ) serves as a model for plant sex chromosome evolution, given that it has recently evolved an XX/XY sex chromosome system. In order to elucidate the molecular basis of gender differences and sex determination, we used RNA‐sequencing (RNA‐Seq) to identify differentially expressed genes between female (XX), male (XY) and supermale (YY) individuals. We identified 570 differentially expressed genes, and showed that significantly more genes exhibited male‐biased than female‐biased expression in garden asparagus. In the context of anther development, we identified genes involved in pollen microspore and tapetum development that were specifically expressed in males and supermales. Comparative analysis of genes in the Arabidopsis thaliana, Zea mays and Oryza sativa anther development pathways shows that anther sterility in females probably occurs through interruption of tapetum development before microspore meiosis.